Assigning sports development to the youth A critique of the LGU-based development program. Proceedings of the 1st Human Movement Scientific Symposium, UP Los Baños, Laguna, pp. 96-104 - Mendoza, M. E. T.; Amparo, J. S. (2003)
The study investigated the assignment of LGU-led sports development programs at the barangay level and analyzed the implications of the dominant assignment to development planning and the plight of sport development. Results showed that sport development planning was traditionally treated as a concern only of the youth, with the assignment for sport development given to the barangay Sangguniang Kabataan. The usual content of sports and recreation development program was found to be limited to the holding of sports league and lacking in more sustainable and high impact programs. No conceptualization of sports as a health strategy for other sectors of the community was found. Recommendations include the reconceptualization of sport development as an integral aspect of other development concerns such as environment, health, gender and development and the elderly; implementation of a community-based physical fitness program which would include sports activities for various sectors of the community; and inclusion of sports and fitness development into health and wellness programs of health agencies.
Keywords: Sports Development Program